Ellsworth Kelly in San Francisco - Grynsztejn, Madeleine; Myers, Julian; San Francisco Museum of Modern Art, San Francisco (Los Angeles : University of California Press, 2002)
This sweeping overview of Ellsworth Kelly's fifty-year career is the first to bring together the twenty-two pieces the San Francisco Museum of Modern Art acquired from Kelly's personal collection in 1999. The volume also includes paintings, sculptures, collages, drawings, and reliefs from the Museum's previous holdings and private collections throughout the San Francisco Bay Area. The primary text by Madeleine Grynsztejn explores the evolution of Kelly's artwork, his longstanding interest in the phenomenology of vision, and his experimentation with compositions generated by the laws of chance. Short essays by Julian Myers examine key issues and groupings of works, from Kelly's early figural paintings through the shaped panels and relief paintings for which the artist is best known. Produced to accompany the exhibition of the same name, Ellsworth Kelly in San Francesco is an elegant presentation of the most significant collection of this artist's work and secures Kelly's place as one of the most original of American artists. Kelly's paintings and sculptures are recognized as vital to the evolution of postwar modernism. One of the chief proponents of abstraction during the 1950s, Kelly is also celebrated for his large-scale monochrome canvases. He first gained critical recognication in the mid 1950s when the Whitney Museum of American Art in New York purchased his work and the Betty Parsons Gallery presented his first solo exhibition in the U.S. From the 1970s to the present,the scale of Kelley's work increased as he joined canvases of different sizes and shapes into asymmetrical formats and created sculptures in bronze, wood and steel. Today Kelly's works are represented in museums and private collections worldwide, and he has received several prestigious awards and honorary degrees.
Ellsworth Kelly in San Francisco, San Francisco Museum of Modern Art, San Francisco, 13 July 2002 - 5 January 2003
Engels
boek
Keywords: Kelly, Ellsworth